Geçmişten Günümüze Rehabilitasyonda Balneoterapi ve Hidroterapi - Sezgin, Nalan; Topçu, Esra; Artuç, Şahide Eda; Kılınç Kamacı, Gizem; Ertem, Uğur; Karakaş, Merve; Akaltun, Mazlum Serdar; Cansu, Döne; Baygutalp, Fatih; Demir Karakılıç, Gülseren; Akyıldız Tezcan, Ezgi; Türemenoğulları, Bengü; et al. (Academician Publishing Book DOI Portal, 2024)
-